Pemetaan Kajian Smart Village dalam Mendukung Pembangunan Berkelanjutan: Analisis Bibliometrik pada Tiongkok, India, dan Indonesia - Musbichatul Chair; Aluisius Hery Pratono (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Research on smart villages has grown substantially alongside the global sustainable development agenda, yet the intellectual structure, thematic evolution, and country-specific research orientations remain insufficiently synthesized. A bibliometric approach was employed to examine the development of smart village literature related to sustainable development using publications retrieved from the Crossref database through Publish or Perish. Following data screening and cleaning procedures, the dataset was analyzed with VOSviewer using keyword co-occurrence analysis to identify relationships among keywords and thematic research clusters. The analysis revealed three dominant clusters representing technology-driven transformation, governance and institutional development, and community-based socioeconomic empowerment. Publications associated with China primarily emphasize digital transformation, artificial intelligence, the Internet of Things, and technological infrastructure. Indonesian studies predominantly focus on governance, institutional capacity, Village SDGs implementation, and participatory rural development, whereas research related to India highlights community empowerment, digital literacy, social inclusion, and improvements in rural livelihoods. These findings demonstrate that smart village development follows diverse pathways shaped by institutional settings, development priorities, and local socioeconomic characteristics rather than a universal model. The study contributes by proposing an integrated conceptual framework that combines technological innovation, governance capacity, and community participation as complementary dimensions supporting sustainable rural development. The findings also provide valuable references for future research and evidence-based policymaking to strengthen sustainable smart village initiatives across different national contexts.